Bioethics Education on Medical Students: Opinions About Ethical Dilemmas - Martins, Vera; Santos, Cristina; Ricou, Miguel; Bataglia, Patrícia [UNESP]; Duarte, Ivone (SAGE Publications, 2021)
Medical education aims to train professionals who are capable of making extremely complex decisions. As part of the medical curriculum, bioethics education could have an important role in promoting moral development and decision-making in medical students. This study aims to determine if, after a Bioethics and Professional Deontology course, medical students would present a change of opinion on three ethical dilemmas. A quantitative and longitudinal study was developed by applying the MCTxt (Moral Competence Test extended), composed of three ethical dilemmas (Worker, doctor, and judge dilemmas), to a sample of 70, fourth year medical students, from a Portuguese medical school. The questionnaire was applied at the beginning and end of a bioethics course, with a 3 month time interval. For this study the opinion scores were analyzed and described using the mean and standard deviation. The comparison of these scores, at both times, were performed using t-tests for paired samples. A significance level of 5% was used. For students who were neutral in the first application, the majority went on to agree or disagree with the performance of the dilemma character, ultimately showing less indecision at the end of bioethics course. The results suggest that, after the bioethics course, students have lower indecision, however the changes were very tenuous. Bioethics education is important to promote more opportunities for reflection and discussion, to stimulate critical judgment, and the ability to make decisions by medical students. Further research could help to better understand this subject.
Keywords: bioethics; decision-making; medical students; moral development; opinion; teaching